2017
DOI: 10.1177/0164027517701447
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Education in the Relationship Between Age of Migration to the United States and Risk of Cognitive Impairment Among Older Mexican Americans

Abstract: Prior research indicates age of migration is associated with cognitive health outcomes among older Mexican Americans; however, factors that explain this relationship are unclear. This study used eight waves from the Hispanic Established Populations for the Epidemiologic Study of the Elderly to examine the role of education in the risk for cognitive impairment (CI) by nativity, age of migration, and gender. Foreign-born women had a higher risk for CI than U.S.-born women, regardless of age of migration. After a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 72 publications
3
22
0
Order By: Relevance
“…The present analysis provides evidence that the relationship between age of migration and risk for cognitive impairment may differ by gender. These findings are supported by previous research that has found a strong association between age of migration, gender and cognitive functioning ( Hill, Angel, & Balistreri, 2012 ; Hill, Angel, Balistreri, et al, 2012 ), prevalent cognitive impairment ( Downer et al, 2017 ), and life expectancies with cognitive impairment ( Garcia, Saenz, et al, 2017 ). Our study advances this literature by documenting differences by age of migration and gender for the incidence of cognitive impairment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present analysis provides evidence that the relationship between age of migration and risk for cognitive impairment may differ by gender. These findings are supported by previous research that has found a strong association between age of migration, gender and cognitive functioning ( Hill, Angel, & Balistreri, 2012 ; Hill, Angel, Balistreri, et al, 2012 ), prevalent cognitive impairment ( Downer et al, 2017 ), and life expectancies with cognitive impairment ( Garcia, Saenz, et al, 2017 ). Our study advances this literature by documenting differences by age of migration and gender for the incidence of cognitive impairment.…”
Section: Discussionsupporting
confidence: 88%
“…Research has only recently begun to examine how cognitive functioning for older Hispanics may differ by nativity status ( Downer, Garcia, Saenz, Markides, & Wong, 2017 ; Garcia, Downer, et al, 2017 ; Garcia, Saenz, et al, 2017 ; Garcia et al, 2018 ; Hill, Angel, & Balistreri, 2012 ; Hill, Angel, Balistreri, & Herrera, 2012 ; Weden et al, 2017 ). An analysis of the Health and Retirement Study revealed that foreign-born Mexican-Americans had a 36% lower risk for incident cognitive impairment than non-Hispanic whites independent of age, gender, and socioeconomic characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators found that older age at migration was associated with higher risk for cognitive impairment, and that education significantly mediated the association between age of migration and cogni-tive impairment. 34 It is possible that, in our present study, the older Latinos without a high school education had higher odds of memory problems for other reasons-such as age of migration, acculturation, nativity, or languages-that were not included in these analyses. Future research should examine the effect of these and related characteristics on subjective cognitive concerns, like self-reported memory problems, and prevalence and severity of cognitive impairment.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, this type of data has been reported in more general rural contexts [27]. The above is argued based on the demographic characteristics of the population, where age represents a fundamental determinant in this type of performance in ethnic groups, whose gradual increase tends to decrease the ability to solve problems and process new information [32].…”
Section: Discussionmentioning
confidence: 58%